Support workers and nursing associates as coaches. Issue 1 (2nd January 2019) - Stonehouse, David
Abstract : This article examines the important role that support workers and nursing associates play in being a coach for other less experienced team members. There is a difference between being a coach and being a mentor and this will be explored. The requirement to be a coach is laid down in both the Code of Conduct for Healthcare Support Workers and Adult Social Care Workers in England (Skills for Care and Skills for Health, 2013 ) and for nursing associates in the recently amended Nursing and Midwifery Council(NMC) (2018) code. Relevant sections of these two codes will be highlighted. The article will then move on to discuss the importance of planning in advance, so that the best support and development can be attained. Reflection at the end by both the coach and learner is key.